Implementasi Moderasi Beragama dalam Menangani Perbedaan Pandangan dan Sikap Civitas Akademika - Syaikon, Muhammad (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2023)
This research aims to determine the application of religious moderation in managing differences of opinion and attitudes among the academic community. Religious moderation is an approach that prioritizes dialogue, tolerance and respect for differences in religious life. This research uses a qualitative approach by analyzing data from interviews with the academic community, observations, and literature reviews related to religious moderation practices. Research findings show that the application of religious moderation to overcome differences of opinion and attitudes among the academic community can be achieved through a number of strategies. One solution is to create a space for open dialogue and discussion that encourages acceptance and respect for differences. Apart from that, involving the academic community in interfaith collaboration is also an effective way to increase understanding and tolerance between individuals. Implementing educational programs that prioritize cross-cultural understanding and cooperation will be an important step in maintaining peace and harmony in the academic environment. Additionally, it is important to involve relevant institutions and organizations in developing policies and regulations that support peaceful religious practices. This study contributes to understanding the importance of practicing religious moderation to address disparities in academic contexts. The results of this research can be a basis for developing more effective strategies to create an inclusive and harmonious environment for university communities with diverse religious backgrounds.